THE EFFECT OF LATE DELIVERY OF PARTS AGAINST SHIP OPERATIONS AT PT. SUMBERBUMI GLOBAL NIAGA - Vidya Selasdini; Sursina Sursina; Hasna Fariz (Dinasti International Journal of Education Management And Social Science, 2021)
The sea transportation system plays a very important role in a country's economy. but there are still a number of issues that are of concern to commercial companies such as late delivery of spare parts and ship operations that occur at PT. Sumberbumi Global Niaga. Based on these problems the authors also conducted an analysis to determine whether there is an effect of the late delivery of spare parts to the ship's operations. The author uses quantitative research methods. With a total sample of 12 items. In searching for the calculation results the authors conducted several data analyzes with the results of the correlation test of 0.897 (rxy = 0.897) which proved that a positive correlation exists. And while tcount = 6,812 (6,812> 1,812) and fcount = 17.14 (17.14> 4.96), where if tcount> ttable and fcount> ftabel Linear regression equation is Y = A + bX, then there is a significant relationship between variable late delivery of spare parts against ship operations. Therefore, the results of the study showed that the late delivery of spare parts proved to be significant for ship operations at PT. Sumberbumi Global Niaga. The author also explained several solutions, namely by applying additional spare parts or backup. The goal is as an anticipation if there is a lack of supply of ship parts, so that ship operations are not disrupted if there is a lead time on spare parts.